2013
DOI: 10.1214/12-aop814
|View full text |Cite
|
Sign up to set email alerts
|

Optimal transport from Lebesgue to Poisson

Abstract: This paper is devoted to the study of couplings of the Lebesgue measure and the Poisson point process. We prove existence and uniqueness of an optimal coupling whenever the asymptotic mean transportation cost is finite. Moreover, we give precise conditions for the latter which demonstrate a sharp threshold at d=2. The cost will be defined in terms of an arbitrary increasing function of the distance. The coupling will be realized by means of a transport map ("allocation map") which assigns to each Poisson point… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…As a special case of our result, we recover the results by Huesmann and Sturm in [HS10]. They studied couplings between the Lebesgue measure and an equivariant point process of intensity β ∈ (0, 1].…”
Section: Introduction and Statement Of Main Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…As a special case of our result, we recover the results by Huesmann and Sturm in [HS10]. They studied couplings between the Lebesgue measure and an equivariant point process of intensity β ∈ (0, 1].…”
Section: Introduction and Statement Of Main Resultssupporting
confidence: 82%
“…They showed that there is a unique optimal semicoupling and also proved an approximation result by solutions to transport problems on bounded regions. Furthermore, in [HS10] necessary and sufficient conditions have been derived implying the finiteness of the mean asymptotic transportation cost in the case of transporting the Lebesgue measure to a Poisson point process. By applying the same techniques similar estimates can be achieved for the case of a compound Poisson process with iid weights (X i ) i∈N , i.e.…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 99%
“…Let us close this note by pointing out that in dimension d ≥ 3, the optimal transport plans corresponding to a very closely related optimal matching problem, have been used in [21] to construct in the limit L → ∞, a stationary and locally optimal coupling between the Poisson point process on R d and the Lebesgue measure. For d = 2, such a coupling is expected not to exist.…”
Section: Application To the Optimal Matching Problemmentioning
confidence: 99%
“…The landmark in this topic is [3] which generalizes [10] to arbitrary dimensions. There are several other constructions in the literature for the case of simple point processes, such as gravitational allocation [1], optimal transport [6], one-sided stable allocation on the line [9], etc.…”
Section: Stable Transports Between Stationary Random Measuresmentioning
confidence: 99%